Mitigating the Problems of Displaced People: Highlighting the Role of Professional Social Workers (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
The displacement of people due to development projects a common international phenomenon. People that are displaced are quite vulnerable. They frequently live in poverty, endure severe deprivation and face discrimination. It is the responsibility of state to provide all relief and rehabilitation facilities to such citizens. There is an explicit and comprehensive policy for the displaced people in India. The objectives of this policy are to minimize displacement and promote, as far as possible, non- displacing or least displacing alternatives. However, no such document/policy can address every problem of the people in totality. The people continue to suffer one or the other problems which requires additional efforts of the non-governmental institutions/social workers/volunteers. In this study, the focus is mainly on the role of social workers towards mitigating the problems of the people displaced by Hydro Power Projects in Himachal Pradesh. Social workers use their professional skills in addressing the problems of individual’s such as mal adjustment and other daily life issues by using the methods of social case work, group work and community organization. Social workers are equipped with knowledge and technical skills that are required to deal with suffering due to any natural or manmade hardship. This paper is based on secondary source of data and the aim of the paper is to highlight the role of social work intervention towards this end.